Land Ownership of the Palace in Kazan District in the Second Half of 16th – Early 17th Century - Smirnov Aleksandr Sergeevich (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2016)
The research is devoted to the analysis of the landownership system of palace in Kazan district in the second half of the 16th century. The author dwells upon the features of palace village such as the granary or the Orthodox church. The church was mandatory attribute for villages with the local population professing the Orthodox religion. The next passage covers the information on the legal status of the land of the palace in the legislation and the cadasters.